The problem of state support and increasing the investment attractiveness of agriculture - Lopatynskyi, Yurii; Nianko, Viktoriia; Purtov, Vladimir; Yekimov, Sergey; Nemtsova, Alla (IOP Publishing, 2021)
Investing in the agricultural sector of the economy largely depends on how quickly the investments made will pay off. Private business, first of all, will invest in the agricultural business in the presence of a low cost and high quality of products. The longer the payback period of the investment, the less likely it is that it will be implemented in practice. Investments are an important source of expanding agricultural production. They enable the agricultural enterprise to carry out technical re-equipment and implement effective environmental and resource-saving technologies. State support for agriculture can consist in the development of transport infrastructure in rural areas, improving the quality of life in rural areas and increasing the labor potential of rural residents. One of the main goals of state support for agriculture is to create favorable conditions for attracting private investors to this industry. Investment activities in agriculture can be focused on improving the fertility of land resources used in agricultural production. The authors consider it expedient to provide the Central Bank with preferential conditions for commercial banks to reduce the cost of loans issued to agricultural enterprises.
-
Keywords: state support, agriculture, investment attractiveness